1987
DOI: 10.1002/ijc.2910390411
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ebv‐carrying b‐cell populations in healthy seropositive individuals with regard to density, release of transforming virus and spontaneous outgrowth

Abstract: Peripheral or tonsil lymphocyte populations of EBV-seropositive donors give rise to EBV-carrying LCLs upon in vitro explantation. Such lines can arise either by a 2-step mechanism, namely release of virus from some of the explanted cells followed by infection of previously uninfected B cells, or by direct outgrowth of virus-harboring B cells (Rickinson et al., 1974; Dalens et al., 1975; Hinuma and Katsuki 1978; Katsuki et al., 1979). We observed that cells responsible for both the 2-step mechanism and for dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Early studies using spontaneous in vitro outgrowth from T cell-depleted PBMC populations from normal donors show that this is predominantly a two-step process where virus-carrying cells undergo lytic infection early in the culture period and the virus released infects and immortalizes co-cultured normal B cells (Rickinson et al, 1977). This process is inhibited by the drug acyclovir, which blocks lytic reactivation (Collins, 1983), and by neutralizing antibody, which prevents secondary infection ; only very rarely have B cells capable of direct outgrowth in culture been detected (Lewin et al, 1987). Outgrowth of LCL is also prevented by co-cultured, autologous T cells which contain an EBV-specific cytotoxic population (Moss et al, 1978) and these cells are therefore removed or inactivated prior to culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies using spontaneous in vitro outgrowth from T cell-depleted PBMC populations from normal donors show that this is predominantly a two-step process where virus-carrying cells undergo lytic infection early in the culture period and the virus released infects and immortalizes co-cultured normal B cells (Rickinson et al, 1977). This process is inhibited by the drug acyclovir, which blocks lytic reactivation (Collins, 1983), and by neutralizing antibody, which prevents secondary infection ; only very rarely have B cells capable of direct outgrowth in culture been detected (Lewin et al, 1987). Outgrowth of LCL is also prevented by co-cultured, autologous T cells which contain an EBV-specific cytotoxic population (Moss et al, 1978) and these cells are therefore removed or inactivated prior to culture.…”
Section: Discussionmentioning
confidence: 99%
“…This technique estimates the level of EBVcarrying B cells in the circulation at 1 : 10& to 1:10' (Lam et al, 1991). In this in vitro assay system, outgrowth of LCL can be suppressed by the viral DNA polymerase inhibitor acyclovir I. Johannessen and others I. Johannessen and others (Collins, 1983), or by serum containing neutralizing antibody, indicating that they arise indirectly by release of virus from the in vivo EBV-carrying B cells and infection of bystanding normal B cells (Rickinson et al, 1977 ;Lewin et al, 1987). Thus, only cells with the capacity to enter a productive cycle in culture are measured in this assay.…”
Section: Introductionmentioning
confidence: 99%
“…The normal precursor of the BL cell is a likely candidate for this role. Lewin et al (1987) showed I. ERNBERG AND OTHERS recently that small, high density B cells from EBV-positive peripheral blood are capable for direct spontaneous outgrowth of LCLs carrying EBV, although this occurs infrequently. These small, presumably long-lived resting B cells in GO may be the cells with a high intrinsic methylation activity, carrying latent viral genomes in vivo in healthy EBV seropositive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine latent gene products detected in vitro, only EBNA1 and LMP2A transcripts are reproducibly detected in latently infected human B cells (6,34,40,46). Although latent virus has been isolated from peripheral B cells in otherwise healthy individuals (1,6,8,15,34,35,40,46), latently infected B cells may reside in bone marrow or other lymphatic sites producing latently infected progeny cells which account for the stable number of infected peripheral B cells in otherwise healthy individuals (21,23,35,50,51).…”
Section: Epstein-barr Virus (Ebv) Is Able To Infect Primary Human B Cmentioning
confidence: 99%